Tropism ablation and stealthing of oncolytic adenovirus enhances systemic delivery to tumors and improves virotherapy of cancer. (November 2012) - Green, Nicola K; Hale, Ashley; Cawood, Ryan; Illingworth, Sam; Herbert, Chris; Hermiston, Terry; Subr, Vladimir; Ulbrich, Karel; van Rooijen, Nico; Seymour, Leonard W; Fisher, Kerry D
Intravenous delivery of therapeutic virus particles remains a major goal for virotherapy of metastatic cancer. Avoiding phagocytic capture and unwanted infection of nontarget cells is essential for extended plasma particle kinetics, and simply ablating one or the other does not give extended plasma circulation. Here we show that polymer coating of adenovirus type 5 (Ad5) can combine with predosing strategies or Kupffer cell ablation to achieve systemic kinetics with a half-life >60 min, allowing ready access to peripheral tumors. Accumulation of virus particles within tumor nodules is proportional to the area under the plasma concentration/time curve. Polymer coating wild-type Ad5 in this way is known to decrease hepatic toxicity, increasing the dose of virus particles that can be safely administered. Using polymer-coating technology to deliver a replicating Ad5 systemically, virus replication and transgene expression was almost totally confined to tumor tissues, giving a much improved therapeutic index compared with uncoated virus, and complete control of human HepG2 tumor xenografts.